Diagnostic Concordance between DSM-5 and ICD-10 Cannabis Use Disorders. (July 2016) - Proctor, Steven L.; Williams, Daniel C.; Kopak, Albert M.; Voluse, Andrew C.; Connolly, Kevin M.; Hoffmann, Norman G.
Abstract: Objectives: With the recent federal mandate that all U.S. health care settings transition to ICD-10 billing codes, empirical evidence is necessary to determine if the DSM-5 designations map to their respective ICD-10 diagnostic categories/billing codes. The present study examined the concordance between DSM-5 and ICD-10 cannabis use disorder diagnoses. Method: Data were derived from routine clinical assessments of 6871 male and 801 female inmates recently admitted to a state prison system from 2000 to 2003. DSM-5 and ICD-10 diagnostic determinations were made from algorithms corresponding to the respective diagnostic formulations. Results: Past 12-month prevalence rates of cannabis use disorders were comparable across classification systems. The vast majority of inmates with no DSM-5 diagnosis continued to have no diagnosis per the ICD-10, and a similar proportion with a DSM-5 severe diagnosis received an ICD-10 dependence diagnosis. Most of the variation in diagnostic classifications was accounted for by those with a DSM-5 moderate diagnosis in that approximately half of these cases received an ICD-10 dependence diagnosis while the remaining cases received a harmful use diagnosis. Conclusions: Although there appears to be a generally high level of agreement between diagnostic classification systems for those with no diagnosis or those evincing symptoms of a more severe condition, concordance between DSM-5 moderate and ICD-10 dependence diagnoses was poor. Additional research is warranted to determine the appropriateness and implications of the current DSM-5 coding guidelines regarding the assignment of an ICD-10 dependence code for those with a DSM-5 moderate diagnosis. Highlights: Concordance between DSM-5 and ICD-10 cannabis use disorders was examined. Past 12-month cannabis use disorder prevalence rates were comparable across systems. Concordance between DSM-5 mild and ICD-10 harmful use diagnoses was fair to good. Concordance between DSM-5 moderate and ICD-10 dependence diagnoses was poor. Concordance between DSM-5 severe and ICD-10 dependence diagnoses was excellent.